Aftermath of the sovereign debt crisis, the new challenges to competitiveness in Portugal - Gonçalves, Vítor da Conceição (2022)
This paper focuses on the interconnections between sovereign debt and the competitiveness of nations in the aftermath of the recent sovereign debt crises in the Eurozone. Further, it identifies new challenges to improving competitiveness. Based on a deductive approach, we analyse secondary data regarding sovereign debt and competitiveness in 28 EU countries for the period from 2006 to 2017. We also look at the recent theoretical developments in the competitiveness of companies, nations, and regions with the goal of identifying the new challenges to Portuguese competitiveness. In the period under analysis, Greece, Ireland, and Portugal had considerable losses in competitiveness and increases in their sovereign debt ratio. Despite benefiting directly from Porter’s insights into improving the country’s competitiveness, the Portuguese sovereign debt ratio has increased steeply. A previous analysis identified a path; however, there are new challenges such as those associated with EU competitiveness, shared value, and smart connected products. These need to be considered to support the creation of new strategies and policies for a small and open economy. Based on our analysis, we argue that competitiveness-oriented policies must more explicitly consider the negative implications of sovereign debt, and must recognize the new challenges to competitiveness.